The conceptual significance of the prefatory sugya in the Babylonian Talmud - Brandes, Yehudah (Journal of Jewish studies, 2018)
The prefatory sugya is unique in that the Mishnah is treated as a canonical text to be interpreted homiletically like a biblical verse. In this article I shift the scholarly focus from the technical interpretative methods of the prefatory sugya to its internal meaning. Homiletical interpretation of the Mishnah is merely a rhetorical device employed by the author of the prefatory sugya in order to provide a conceptual preface to the tractate as a whole or to the central topic of the opening chapters. With this approach, the possibility emerges that the Talmudic prefatory sugya may have preceded the Savoraim, and may be considered a natural extension of the familiar petihta Midrash genre. This new 'content approach' significantly shifts and enriches our perception of the literary role of the prefatory sugya, from a playful intellectual curiosity to meaningful dicta of the sages emphasizing essential principles and values of the tractate.